Changes in Doppler indices of cardiac function during and after percutaneous transluminal coronary angioplasty. Issue 5 (November 1991) - Hunt, A C; Chow, S C; Escaned, J; Perry, R A; Seth, A; Shiu, M F
Abstract : OBJECTIVE--To assess the sensitivities of Doppler indices to changes in global cardiac function during and after controlled myocardial ischaemia induced by coronary angioplasty. DESIGN--Continuous wave Doppler signals of aortic flow were recorded during coronary angioplasty. The following Doppler indices of cardiac function were measured before, during, and after balloon inflation: V (peak velocity), MA (mean acceleration), V2/T (T = time from onset to peak ejection), and MD (minute distance corrected for baseline heart rate). SETTING--A tertiary care cardiological unit in a university hospital. PATIENTS--Sixteen patients undergoing coronary angioplasty of the left anterior descending coronary artery. Eight patients had multivessel disease. MAIN OUTCOME MEASURES--The primary outcome measures were planned before data collection began. RESULTS--12 patients showed a significant fall of three or more Doppler indices from their baseline values during balloon inflation. This occurred in all patients with multivessel disease. The Doppler indices V2 T, MD, V, and MA fell by 43.7%, 37.7%, 27.4%, and 23% respectively from their baseline values (p less than 0.0001). The relative sensitivities of the Doppler indices to ischaemia were V2/T greater than MD (p less than 0.02), MD greater than (p less than 0.001), and V greater than MA (p less than 0.01). The impairment of global left ventricular function resulting from brief balloon inflation during single vessel angioplasty was reversible in all the patients. CONCLUSIONS--The Doppler indices V2/T, MD, V, and MA are all sensitive, in order of magnitude, to falls in global cardiac function resulting from ischaemia. They may prove useful for assessing cardiac function during ischaemia in the clinical setting.